2006
DOI: 10.1002/hlca.200690193
|View full text |Cite
|
Sign up to set email alerts
|

The Binary System Tetradecanedioic Acid–Hexadecanedioic Acid: Polymorphism of the Components and Experimental Phase Diagram

Abstract: Complementary techniques had to be applied to investigate the binary system tetradecanedioic acid (C 14 H 26 O 4 )-hexadecanedioic acid (C 16 H 30 O 4 ), because all the forms observed have the same space group (P2 1 /c; Z = 2). We studied the polymorphism of the two single compounds and of their mixtures by X-ray powder diffraction, differential-scanning calorimetry (DSC), infrared spectroscopy (IR), scanning electron microscopy (SEM), and thermo-optical microscopy (TOM). The two diacids were found to be isop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(11 reference statements)
1
7
0
2
Order By: Relevance
“…Lauric acid and myristic acid present light inflection thermal event also observed by Maximo et al and Costa et al [25,27]. As reported by Ventolà et al [35], this light inflection suggests the presence of a solid-solid transition overlapping the solid-liquid phenomena highlighted by black arrow (see inserts in Fig. 1).…”
Section: Sle Thermodynamic Modelingsupporting
confidence: 59%
See 1 more Smart Citation
“…Lauric acid and myristic acid present light inflection thermal event also observed by Maximo et al and Costa et al [25,27]. As reported by Ventolà et al [35], this light inflection suggests the presence of a solid-solid transition overlapping the solid-liquid phenomena highlighted by black arrow (see inserts in Fig. 1).…”
Section: Sle Thermodynamic Modelingsupporting
confidence: 59%
“…In the same figure, it is possible to observe that fatty alcohols (1-decanol, 1-dodecanol and 1-tetradecanol) also exhibit overlapped peaks and triolein showed two well-defined peaks in the temperature range studied. According to literature by Ventolà et al [35], the presence of overlapped peaks can indicate that polymorphic transitions probably occurred during the melting processes of these fatty compounds; thus, determining the transition enthalpy by means of peak area measurement does not lead to accurate and reliable values [27]. [27] 311.39 [27] 47.60 [27] a Uncertainty of melting temperature and molar enthalpy of fusion AE 0.30 K and AE 0.037 kJ mol À1 , respectively.…”
Section: Sle Thermodynamic Modelingmentioning
confidence: 99%
“…[11e13]. Ventol a et al [26] analyzed similar compounds and suggested that the inflection points observed in the melting peak are due to the presence of solidesolid transitions overlapping the solideliquid transition. According to Leitão et al [27], these transitions can be ascribed to the transition between single crystalline forms, mixtures of several polymorphic forms or amorphous states.…”
Section: Resultsmentioning
confidence: 99%
“…This planar alignment of the molecules promotes molecular self-organization into structures dominated by the lateral interactions of their various moieties, in particular the HBs between the molecules’ craboxyl end groups. However, as for all 2D structures, the X-ray GID patterns presented above, although having considerably more peaks than those of most liquid-supported interfacial layers, ,,, have still much fewer peaks than the diffraction patterns of 3D single crystals or powders of the same compounds, which may contain hundreds to thousands of lines. ,− Thus, the elucidation of fine details in the headgroup and the chain ordering from our GID patterns is more prone to ambiguities and uncertainties. Using additional information from relevant 2D or 3D system can, however, enhance considerably the confidence and validity of the extracted structure.…”
Section: Discussionmentioning
confidence: 94%